2000
DOI: 10.1042/0264-6021:3450017
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of c-Src by prolactin is independent of Jak2

Abstract: Interaction of prolactin (PRL) with its receptor (PRLR) leads to activation of Jak and Src family tyrosine kinases. The PRL/growth hormone/cytokine receptor family conserves a proline-rich sequence in the cytoplasmic juxtamembrane region (Box 1) required for association and subsequent activation of Jaks. In the present work, we studied the mechanisms underlying c-Src kinase activation by PRL and the role that Jak2 plays in this process. PRL addition to chicken embryo fibroblasts (CEF) expressing the rat PRLR l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…Surprisingly, the molecular analysis of JAK2 deficient mammary epithelial cells revealed that the SRC tyrosine kinase, the focal adhesion kinase (FAK), and MAP kinases could still be effectively activated in response to PRL stimulation (Sakamoto et al, 2007). This finding supports previous observations by Fresno Vara and colleagues (2000) that the PRLR-mediated activation of the c-SRC kinase occurs independently of JAK2 in human breast cancer cells. Since JAK2 deficient mammary epithelial cells lack active STAT5, it is evident that SRC does not activate STAT5 directly in a JAK2-independent manner.…”
Section: Evidence For a Crosstalk Between Active Stat5 And Pi3k/akt Isupporting
confidence: 93%
“…Surprisingly, the molecular analysis of JAK2 deficient mammary epithelial cells revealed that the SRC tyrosine kinase, the focal adhesion kinase (FAK), and MAP kinases could still be effectively activated in response to PRL stimulation (Sakamoto et al, 2007). This finding supports previous observations by Fresno Vara and colleagues (2000) that the PRLR-mediated activation of the c-SRC kinase occurs independently of JAK2 in human breast cancer cells. Since JAK2 deficient mammary epithelial cells lack active STAT5, it is evident that SRC does not activate STAT5 directly in a JAK2-independent manner.…”
Section: Evidence For a Crosstalk Between Active Stat5 And Pi3k/akt Isupporting
confidence: 93%
“…Previous studies have shown that Src‐kinase is activated by different cytokines 63. Src kinase has been shown to be stimulated by the prolactin receptor, which belongs to the class I cytokine receptor family, independently of JAK2 42. Similar results have been shown for growth hormone 64.…”
Section: Discussionsupporting
confidence: 66%
“…Src kinase is activated by the class I cytokine receptor family, as shown for the prolactin receptor,42 and is involved in the regulation of cell motility 43. We used a specific Src kinase inhibitor‐Src kinase inhibitor II (SrcKI‐II), to investigate whether Src kinase is involved in leptin stimulation of Rho GTPase activity.…”
Section: Resultsmentioning
confidence: 99%
“…Activated Stats dimerize, translocate into the nucleus, and bind to specific sequences on target genes [123]. The Src family kinases and the ras/raf/mitogen-activated protein kinase (MAPK) cascade are also activated by PRL [124], directly stimulating proliferation and modulating Stat activity [125]; however, they appear to be less important than the Jak-Stat pathway for transducing the effects of PRL.…”
Section: Prl and Gh Signaling Pathwaysmentioning
confidence: 98%